Energy storage modification of coal gangue and its application in high-specific-energy batteries - Zhihui SUN; Yunbo WANG; Shuxuan MA; Meng LI (Meitan kexue jishu)
The electrochemical energy storage utilization of coal gangue robustly supports the synergetic energy development of the coal mining industry, while addressing solid waste disposal issues, offering a forward-looking solution for the resourceful utilization of mining solid waste and the promotion of green and low-carbon mining. Through refined alkali activation and acid chemical modification techniques, this study innovatively transforming gangue waste into high-value-added energy storage materials and realizing their efficient application in the field of high-specific-energy batteries. The microstructure of modified coal gangue and original gangue was characterized in detail using techniques such as transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS), aiming to reveal the modification mechanism in depth. Through single factor experimental methods, the differences in composition, crystal structure, and local electronic environment between raw coal gangue and modified coal gangue were analyzed in depth, and the optimal conditions for modified coal gangue in energy storage applications were determined. The results indicate that: After modification treatment, a layer of amorphous nano particle Al2O3 activation layer was formed on the surface of coal gangue, effectively reducing energy loss during the electrode reaction process; The surface of modified coal gangue is rich in highly active electrocatalytic sites such as oxygen-containing functional groups and oxygen vacancies, significantly reducing the activation energy of surface reactions. The modified coal gangue exhibits low overpotentials for charging and discharging (1.12 V), high discharge specific capacity (8310 mAh/g), and long cycling stability (>180 h) in lithium-oxygen batteries. Modified coal gangue exhibits flexible and wearable energy storage characteristics, and can still provide stable energy supply even when folded at a 45° angle. The study has important practical significance and application value for promoting the resource utilization of mining waste, reducing environmental pollution, and improving resource utilization efficiency.